Detection of ESBLs and carbapenemases among Enterobacteriaceae isolated from diabetic foot infections in Ouargla, Algeria - Khaldi, Zohra; Nayme, Kaotar; Bourjilat, Fatna; Bensaci, Abdelmadjid; Timinouni, Mohammed; Ould El-Hadj-Khelil, Aminata (The Journal of Infection in Developing Countries, 2022)
Introduction: The emergence and rapid spread of Enterobacteriaceae carrying extended spectrum beta-lactamases (ESBLs) and carbapenemases represent a great threat to clinical treatment due to their multi-drug resistance. This study investigated ESBLs and carbapenemases encoding genes in Enterobacteriaceae collected from diabetic foot infections (DFIs) in Ouargla, southern Algeria. Methodology: A total of 70 Enterobacteriaceae strains were recovered from 76 patients with DFI between February 2017 and April 2018. Antimicrobial susceptibility testing was performed using the disc diffusion method, and the presence of bla genes was detected using polymerase chain reaction (PCR) and DNA sequencing. The genetic transfer of the plasmids was carried out by conjugation using the broth mating method. Results: The most common isolate was Proteus mirabilis, followed by Escherichia coli, Morganella morganii and Klebsiella pneumoniae. The prevalence of ESBL and carbapenemase-producing Enterobacteriaceae was 11.42% and 2.85 % respectively. Plasmid-mediated AmpC was detected in 5.71% isolates. Conjugation experiments showed the transferability of blaCTX-M-2. Conclusions: Our findings support the view that various pathogens found in DFIs differ from one part of the country to another. This study reports the first description of metallo-β-lactamase NDM-5 producing Klebsiella pneumoniae clinical isolate in Algeria.